Do Psycholegal Abilities Mediate the Relationship between Psychiatric Diagnoses and Competence to Stand Trial Opinions?. Issue 1 (1st January 2016) - Stein, Michelle L.; Kan, Lisa Y.; Henderson, Craig E.
ABSTRACT: Studies have examined relationships between (a) diagnoses and evaluator opinion of competence to stand trial (CST), (b) evaluator opinion and psycholegal abilities, and (c) diagnoses and psycholegal abilities. The present study adds to the literature by exploring the mediating role of psycholegal abilities between diagnoses and CST opinions through the examination of 119 CST reports. Findings indicate deficits in psycholegal abilities mediated the relationship between psychotic disorders and opinion of incompetence, but only among unmedicated defendants. Results regarding psycholegal abilities' mediating role in the relationship between cognitive disorder and opinion of incompetence are less clear. We offered several hypotheses for the differences in results, as well as suggestions for future research.